1990
DOI: 10.1159/000186156
|View full text |Cite
|
Sign up to set email alerts
|

Antimouse Laminin Antibodies in IgA Nephropathy and Various Glomerular Diseases

Abstract: IgG, IgA and IgM class antibodies to mouse laminin and human fibronectin in sera from patients with various glomerular diseases (50 cases of IgA nephropathy, 5 cases of minimal-change nephrotic syndrome; 6 cases of membranous nephropathy, 5 cases of systemic lupus erythematosus, 2 cases of Henoch-Schönlein purpura, 3 cases of poststreptococcal nephritis and 4 cases of preeclampsia) and from 30 normal controls were tested using a solid-phase enzyme-linked immunosorbent assay method. IgA antimouse laminin antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…35] and soybean protein by us [36,37]. 400 Sato/Kino/Naheshima/Koshikawa Anti-CD4-t-CD45R + in IgA Nephropathy Autoimmune reactions are also considered as one of the important factors in the pathogenesis of IgA N. Various types of autoantibodies have been recognized, such as cold reacting antinuclear factor [9], antimouse laminin IgA anti body [10]. IgA rheumatoid factor [II], antivascular endothel ial cells [12], anticollagen IgA antibodies [13], Also, it has been reported that some autoimmune diseases or phenome na, i.e., scleritis [38], rheumatoid arthritis [39], sicca syn drome [40], are associated with IgA N. Moreover, it has been claimed that corticosteroids are effective in the treat ment of IgA N [41], This evidence indicates that autoim mune mechanisms participate strongly in the pathogenesis of IgA N. In this study, the presence of antilymphocyte antibodies against CD4 + CD45R+ cells is described in sera of patients with IgA N. CD45R (2H4) antibody subdivides the CD4-I-popula tion into suppressor/inducer(CD44-CD45R + )and helper/inducer (CD4 + CD45R-) subsets [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35] and soybean protein by us [36,37]. 400 Sato/Kino/Naheshima/Koshikawa Anti-CD4-t-CD45R + in IgA Nephropathy Autoimmune reactions are also considered as one of the important factors in the pathogenesis of IgA N. Various types of autoantibodies have been recognized, such as cold reacting antinuclear factor [9], antimouse laminin IgA anti body [10]. IgA rheumatoid factor [II], antivascular endothel ial cells [12], anticollagen IgA antibodies [13], Also, it has been reported that some autoimmune diseases or phenome na, i.e., scleritis [38], rheumatoid arthritis [39], sicca syn drome [40], are associated with IgA N. Moreover, it has been claimed that corticosteroids are effective in the treat ment of IgA N [41], This evidence indicates that autoim mune mechanisms participate strongly in the pathogenesis of IgA N. In this study, the presence of antilymphocyte antibodies against CD4 + CD45R+ cells is described in sera of patients with IgA N. CD45R (2H4) antibody subdivides the CD4-I-popula tion into suppressor/inducer(CD44-CD45R + )and helper/inducer (CD4 + CD45R-) subsets [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various kinds of autoantibodies have been recognized in sera of patients with IgA N, such as cold reacting antinuclear factor [9], antimouse lam inin IgA antibodies [10], IgA rheumatoid factor [II], antivascular endothelial cells [12] and anticollagen IgA antibodies [13], and complexes containing IgA and fibronectin [14]. These abnormalities may participate strongly in the patho genesis a n d /o r the progression of IgA N.…”
Section: Introductionmentioning
confidence: 99%
“…However, these workers did limited studies on the specificity of the antibodies, and none has localized the binding site for the antibodies within the multi-domain Fn molecule. By contrast, a study investigating antibodies to ECM in patients with SLE nephritis failed to detect anti-Fn antibodies [19]. [n viewof limited and variable data on antibodies to Fn and the rnany varied biological Tunctions oi" this ECM protein, we investigated the occurrence and specificity ofanti-Fn antibodies in sera of patients with SLE.…”
Section: Introductionmentioning
confidence: 94%
“…70 These results indicate that alteration of the IgA-FcaRI interaction may play a key role in the development of IgAN. The third mechanism for the formation of IgA complexes in IgAN may involve IgA binding to other circulating proteins such as fibronectin, collagen or laminin, [72][73][74] suggesting an additional mechanism by which IgA complexes bind to mesangium through adhesion to extracellular matrix proteins. In favor of this hypothesis, knockout mice for uteroglobin, a serum protein that controls fibronectin levels, develop IgAN.…”
Section: Iga Dysfunction and Inflammatory Diseases C Papista Et Al 129mentioning
confidence: 99%